Method for preparing quinine anion exchange membrane through pre-irradiation grafting

The quinine ring functional groups are grafted on the linear carbon chain polymer framework of the anion exchange membrane through pre-irradiation grafting technology, which solves the shortcomings of the existing anion exchange membrane in terms of alkali stability and mechanical properties, and achieves high performance and high performance Stable quinine type anion exchange membrane.

CN119455697AActive Publication Date: 2025-02-18TIANJIN UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411466863.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-18
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing anion exchange membrane has shortcomings in alkali stability and mechanical properties, which limits its application in electrolytic water hydrogen production and fuel cells.

Method used

Pre-irradiation grafting technology was used to graft quinine ring functional groups on the linear carbon chain polymer backbone, and a quinine type anion exchange membrane was prepared by electron beam irradiation and grafting reaction.

Benefits of technology

The ionic conductivity and chemical stability of the anion exchange membrane are improved, and its performance and stability in fuel cells and electrolyzed water are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455697A_ABST
    Figure CN119455697A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of anion exchange membranes, and discloses a method for preparing a quinine anion exchange membrane by pre-irradiation grafting, which comprises the following steps: by taking a linear carbon chain polymer as a base material and a vinyl monomer as a grafting monomer, firstly, pre-irradiating the linear carbon chain polymer by an electron beam radiation source; then carrying out a grafting reaction on the pre-irradiated base material in a vinyl monomer solution, and then carrying out a quaternary ammonification reaction on the obtained grafted polymer and a quinuclidine solution, so as to obtain the quinine anion exchange membrane. The method is relatively simple in overall process, mild in reaction condition, relatively short in reaction time and relatively low in cost; compared with a biphenyl quinine anion exchange membrane, the prepared quinine anion exchange membrane has higher anion conductivity and better mechanical strength, and compared with a piperidine anion exchange membrane and a trimethylamine anion exchange membrane, the prepared quinine anion exchange membrane has higher chemical stability; and the material can be applied to the fields of fuel cells, electrolyzed water, flow cells and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anion exchange membranes, and in particular relates to a method for preparing anion exchange membranes by using radiation grafting technology. Background Art

[0002] Anion exchange membranes are widely used in water electrolysis to produce hydrogen and fuel cells. Anion exchange membranes act as channels for hydroxide ion exchange, as well as barriers to prevent contact between hydrogen and oxygen at the anode and cathode, and provide support for the catalyst coating. Therefore, anion exchange membranes need to have extremely high ion conductivity and air tightness, as well as good chemical and mechanical stability. The performance of anion exchange membranes directly affects the operating efficiency and life of anion exchange membrane water electrolysis to produce hydrogen and anion exchange membrane fuel cells.

[0003] Radiation grafting technology is one of the effective means to develop various new materials with excellent properties or to modify the original materials by radiation. The basic principle of radiation grafting copolymerization is to use high-energy radiation to produce several active points on the polymer skeleton, and then successfully graft another vinyl monomer or homopolymer onto these active points to produce side chains. Its main advantages include: radiation grafting is easier to master, operate and control than general chemical grafting; the radiation grafting reaction can control the grafting rate according to the radiation dose and other methods as needed; the radiation grafting reaction is initiated by radiation, and no initiator needs to be added to the grafting system, so a very pure grafted polymer can be obtained. Radiation grafting can be divided into co-irradiation and pre-irradiation. Among them, the pre-irradiation grafting method does not need to purchase expensive radiation sources because irradiation and grafting are two independent processes, so the research and production units do not need to purchase expensive radiation sources, and it is highly economical. In short, the radiation grafting method has been proven to be an economical and efficient technology for synthesizing anion exchange membranes due to its wide range of raw materials, low prices, easy operation of membrane modification, and flexible controllability. Radiation grafting technology has been used by researchers to prepare anion exchange membranes. However, the grafted monomer is mainly benzyltrimethylammonium ion, the overall alkaline stability is insufficient, and the large water absorption and swelling are the main factors restricting its widespread application.

[0004] The polyarylpiperidine anion exchange membrane and its derivatives developed in 2018 have become the mainstream of anion exchange membrane research due to their relatively simple preparation methods, mature preparation processes, and high alkali stability. The alkali stability of polyarylquinine anion exchange membranes developed in the past two years has been further improved. However, the superacid required in its polymerization process limits the reaction conditions and further increases the risk after industrial production. In addition, polyarylpiperidine and its derivatives have high water absorption and swelling and low flexibility. In order to increase their actual use value, fluoroketone monomers need to be introduced to improve their mechanical properties. However, the expensive price of fluoroketone monomers hinders their commercial application prospects.

[0005] In summary, the mainstream polyaryl piperidine and its derivative anion exchange membranes on the market still have many defects and cannot meet the application needs of the market. The anion exchange membrane prepared by irradiation grafting has become an effective means of large-scale preparation of anion exchange membranes due to its high conductivity, simple and controllable preparation method, and low cost. Further improving the alkaline stability of irradiation grafted anion exchange membranes to meet the high efficiency and long life of anion exchange membrane water electrolysis and anion exchange membrane fuel cells is a key issue that needs to be solved in this field. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing quinine-type anion exchange membrane by pre-irradiation grafting technology. The prepared anion exchange membrane has high ion conductivity and high chemical stability, and has high performance and strong stability in anion exchange membrane water electrolysis and anion exchange membrane fuel cell.

[0007] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:

[0008] According to one aspect of the present invention, a method for preparing a quinine-type anion exchange membrane by pre-irradiation grafting is provided, wherein a linear carbon chain polymer is used as a substrate and a vinyl monomer is used as a grafting monomer. The linear carbon chain polymer is first pre-irradiated with an electron beam radiation source, and then the pre-irradiated substrate is subjected to a grafting reaction in a vinyl monomer solution, and then the obtained grafted polymer is subjected to a quaternization reaction with a quinuclidine solution, thereby obtaining a quinine-type anion exchange membrane.

[0009] Furthermore, the linear carbon chain polymer is at least one of ethylene-tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), fluorinated ethylene propylene copolymer (FEP), polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), and hydrogenated styrene-butadiene block copolymer (SEBS).

[0010] Furthermore, the vinyl monomer is at least one of vinylbenzyl chloride, chloromethylstyrene, undecene bromide and octadecene bromide.

[0011] Furthermore, the concentration of the vinyl monomer solution is 5wt.% to 20wt.%, and the solvent is at least one of water, isopropanol, toluene, benzene, and N-methyl-2-pyrrolidone.

[0012] Furthermore, the irradiation energy of the pre-irradiation is 4.5 MeV to 10 MeV, and the total dose is 30 kGy to 150 kGy.

[0013] Furthermore, the vinyl monomer solution includes a solvent whose volume is 2 to 9 times that of the vinyl monomer, and the solvent is at least one of water, isopropanol, toluene, benzene, and N-methyl-2-pyrrolidone.

[0014] Furthermore, the vinyl monomer solution includes a surfactant accounting for 10% to 50% of the volume of the vinyl monomer.

[0015] Furthermore, the concentration of the quinuclidine solution is 3wt.% to 10wt.%.

[0016] Further, the following steps are included:

[0017] (1) subjecting the linear carbon chain polymer to electron beam irradiation at ≤1 atmosphere in air or inert gas; storing the irradiated substrate at ≤-40°C;

[0018] (2) After the vinyl monomer solution in the reactor is deoxygenated by passing an inert gas, the substrate obtained in step (1) is placed in the vinyl monomer solution, and the inert gas is continuously passed into the solution system to exhaust oxygen;

[0019] (3) sealing the reactor and heating it at a constant temperature to carry out a grafting reaction to prepare a grafted linear carbon chain polymer, wherein the constant temperature heating temperature is 40° C. to 80° C. and the time is 4 h to 16 h;

[0020] (4) washing the grafted linear carbon chain polymer in a solvent, and drying it in a vacuum drying oven at 50° C. to 80° C. after washing;

[0021] (5) placing the washed and dried grafted linear carbon chain polymer in a quinuclidine solution at 70° C. to 85° C. for quaternization reaction for 5 to 7 days;

[0022] (6) After the quaternization reaction, the substrate is washed with water and then placed in a NaCl or NaOH solution at room temperature for ion exchange to obtain a quinine-type anion exchange membrane.

[0023] Furthermore, the solvent in step (4) is at least one of water, isopropanol, toluene, ethanol and methanol.

[0024] According to another aspect of the present invention, there is provided a quinine-type anion exchange membrane prepared by pre-irradiation grafting, obtained by the above preparation method.

[0025] The beneficial effects of the present invention are:

[0026] The present invention grafts quinuclidine functional groups on a linear carbon chain polymer skeleton through a pre-radiation grafting technology to enable the polymer to have anion exchange function. The overall process of the method is relatively simple, the reaction conditions are mild, the reaction time is short, and the cost is low. The prepared quinine type anion exchange membrane has higher anion conductivity and better mechanical flexibility than a biphenylquinine anion exchange membrane. The prepared quinine type anion exchange membrane has stronger chemical stability than piperidine type and trimethylamine type anion exchange membranes, so that the polymer can be applied to fuel cells, water electrolysis, flow batteries and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The reaction equation of the ETFE-based quinine anion exchange membrane prepared in Example 1;

[0028] Figure 2 is the hydroxide ion conductivity of the ETFE-based quinine type anion exchange membrane prepared in Example 1;

[0029] Figure 3 The LSV curve of the ETFE-based quinine anion exchange membrane prepared in Example 1 in an alkaline electrolytic cell at 60° C. and 80° C.;

[0030] Figure 4 This is an EIS curve diagram of the ETFE-based quinine anion exchange membrane prepared in Example 1 at 60° C. and 80° C. in an alkaline electrolytic cell. DETAILED DESCRIPTION

[0031] The invention provides a quinine type anion exchange membrane prepared by pre-irradiation grafting and a method thereof. A linear carbon chain polymer is used as a substrate and a vinyl monomer is used as a grafting monomer. The linear carbon chain polymer is pre-irradiated with an electron beam radiation source, and then the pre-irradiated substrate is subjected to a grafting reaction in a vinyl monomer solution. The obtained grafted polymer is then subjected to a quaternization reaction with a quinuclidine solution, thereby obtaining a quinine type anion exchange membrane.

[0032] The specific steps may include:

[0033] (1) subjecting a linear carbon chain polymer to electron beam irradiation at a pressure of ≤1 atmosphere in air or inert gas; and storing the irradiated substrate at a temperature of ≤-40°C;

[0034] (2) After the vinyl monomer solution in the reactor is deoxygenated by passing an inert gas, the substrate obtained in step (1) is placed in the vinyl monomer solution, and the inert gas is continuously passed into the solution system to exhaust oxygen;

[0035] (3) sealing the reactor and heating it at a constant temperature to carry out a grafting reaction to prepare a grafted linear carbon chain polymer, wherein the constant temperature heating temperature is 40° C. to 80° C. and the time is 4 h to 16 h;

[0036] (4) washing the grafted linear carbon chain polymer in a solvent, and drying it in a vacuum drying oven at 50° C. to 80° C. after washing; wherein the solvent is at least one of water, isopropanol, toluene, ethanol, and methanol;

[0037] (5) placing the washed and dried grafted linear carbon chain polymer in a quinuclidine solution at 70° C. to 85° C. for quaternization reaction for 5 to 7 days;

[0038] (6) After the quaternization reaction, the substrate is washed with water and then placed in a NaCl or NaOH solution at room temperature for ion exchange to obtain a quinine-type anion exchange membrane.

[0039] For some preferred embodiments of the present invention, the linear carbon chain polymer is at least one of ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), fluorinated ethylene propylene copolymer (FEP), polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), and hydrogenated styrene butadiene block copolymer (SEBS).

[0040] In some preferred embodiments of the present invention, the vinyl monomer is at least one of vinylbenzyl chloride, chloromethylstyrene, undecene bromide and octadecene bromide.

[0041] For some preferred embodiments of the present invention, the concentration of the vinyl monomer solution is 5 w.t.% to 20 w.t.%.

[0042] For some preferred embodiments of the present invention, the irradiation energy of the pre-irradiation is 4.5 MeV to 10 MeV, and the total dose is 30 kGy to 150 kGy.

[0043] According to some preferred embodiments of the present invention, the vinyl monomer solution includes a surfactant in an amount of 10% to 50% by volume of the vinyl monomer.

[0044] For some preferred embodiments of the present invention, the concentration of the quinuclidine solution is 3 w.t.% to 10 w.t.%.

[0045] The following is a more detailed description of the specific implementation of the present invention in conjunction with the accompanying drawings and embodiments, so as to better understand the scheme of the present invention and its advantages in various aspects. It should be noted that the specific implementation methods and embodiments described below are only for the purpose of illustration, and are not intended to limit the present invention.

[0046] Example 1

[0047] This embodiment provides a method for preparing an ETFE-based quinine type anion exchange membrane, and its specific structure is as follows:

[0048]

[0049] And, follow the steps below:

[0050] 1) The ETFE base film is subjected to electron beam irradiation in air at ≤1 atmosphere; the irradiation energy is 10 MeV and the total dose is 100 kGy;

[0051] 2) storing the irradiated ETFE base film at -40°C;

[0052] 3) Add 5 ml of vinyl benzyl chloride monomer, 1 ml of N-octyl pyrrolidone and 94 ml of deionized water into a Schlenk tube to prepare a grafting monomer solution, and pass argon gas for 30 minutes to deoxygenate;

[0053] 4) placing the ETFE base film stored frozen after irradiation into the grafting monomer solution, and continuing to pass argon gas for 2 hours to exhaust oxygen;

[0054] 5) After the Schlenk tube was sealed, magnetic stirring was performed under argon atmosphere, and the temperature was raised to 70° C. for grafting reaction for 16 h;

[0055] 6) After the grafting reaction, the film turns light yellow and is washed in isopropanol for 1 hour and vacuum dried at 70°C for 5 hours;

[0056] 7) placing the grafted ETFE base film into 120 ml NMP solution containing 5 g quinuclidine and performing quaternization reaction at 80° C. for 5 days;

[0057] 8) placing the quaternized ETFE base membrane in a 1M sodium chloride solution for ion exchange for 24 hours;

[0058] 9) The quinine anion exchange membrane after ion exchange is placed in deionized water for cleaning.

[0059] Figure 1 is the reaction equation of the ETFE-based quinine anion exchange membrane prepared in this embodiment, Figure 1 It is shown that this embodiment is carried out in three steps: irradiation, grafting, and functionalization.

[0060] Figure 2 The hydroxyl ion conductivity of the ETFE-based quinine anion exchange membrane prepared in this example was measured by using an electrochemical impedance spectroscopy at 1-10 5 The anion exchange membrane material is tested in the Hz range and the resulting ohmic resistance is recorded, denoted as R. The conductivity of the sample to be tested can be calculated by the formula:

[0061] σ=L / (A·R)

[0062] The thickness of the sample to be tested is recorded as L, in cm; the contact area between the anion exchange membrane and the electrode is recorded as A, in cm 2 .

[0063] Depend on Figure 2 It can be seen that the ETFE-based quinine anion exchange membrane prepared in Example 1 has a room temperature conductivity higher than 75 mS / cm and a 80° C. conductivity higher than 150 mS / cm. The high conductivity surface of the anion exchange membrane indicates its good application prospects.

[0064] The anion exchange membrane prepared in Example 1 was 2 The IrO2 electrodes and Pt / C electrodes of different sizes were assembled into membrane electrodes and installed in an electrolytic cell. The electrolyte solution was 1M KOH solution. The linear voltammetric scan test was performed using an electrochemical workstation. The results are shown in the figure. Figure 3 As shown. Figure 3 It can be seen that (membrane electrode) at 60℃ 1A / cm 2 The voltage is only 1.64V, and 1A / cm at 80℃ 2 The voltage was only 1.64 V at the current density, demonstrating the excellent water electrolysis performance of the membrane electrode prepared with quinine-type anion exchange membrane.

[0065] Then the two-electrode method was used to test 1A / cm 2 The AC impedance of the membrane electrode prepared with quinine type anion exchange membrane, Figure 4 The EIS curves of the membrane electrode at 60°C and 80°C show that the electrochemical impedance at 60°C is only 0.062Ω, and the electrochemical impedance at 80°C is only 0.051Ω, indicating that the membrane electrode prepared with irradiated grafted quinine anion exchange membrane has lower electrochemical impedance performance.

[0066] Example 2

[0067] This embodiment provides a method for preparing an ETFE-based quinine-type anion exchange membrane, which is carried out according to the following steps:

[0068] 1) The ETFE base film is subjected to electron beam irradiation in air at ≤1 atmosphere; the irradiation energy is 10 MeV and the total dose is 20 kGy;

[0069] 2) storing the irradiated ETFE base film at -80°C;

[0070] 3) Add 10 ml of vinyl benzyl chloride monomer, 1 ml of N-octyl pyrrolidone and 80 ml of deionized water into a Schlenk tube to prepare a grafting monomer solution, and pass argon gas for 30 minutes to deoxygenate;

[0071] 4) placing the ETFE base film stored frozen after irradiation into the grafting monomer solution, and continuing to pass argon gas for 1 hour to exhaust oxygen;

[0072] 5) After the Schlenk tube was sealed, the grafting reaction was carried out for 1 h under argon atmosphere with magnetic stirring and the temperature was raised to 60°C;

[0073] 6) After the grafting reaction, the film turns light yellow and is washed in isopropanol for 1 hour and vacuum dried at 50°C for 16 hours;

[0074] 7) placing the grafted ETFE base film into 100 ml NMP solution containing 8 g quinuclidine and performing quaternization reaction at 60° C. for 3 days;

[0075] 8) placing the quaternized ETFE base film in a 1M sodium hydroxide solution for ion exchange for 24 hours;

[0076] 9) The quinine anion exchange membrane after ion exchange is placed in deionized water for cleaning.

[0077] Example 3

[0078] This embodiment provides a method for preparing a HDPE-based quinine type anion exchange membrane, and its specific structure is as follows:

[0079]

[0080] And, follow the steps below:

[0081] 1) The HDPE base film is subjected to electron beam irradiation in air at ≤1 atmosphere; the irradiation energy is 4.5 MeV and the total dose is 150 kGy;

[0082] 2) storing the irradiated HDPE base film at -80°C;

[0083] 3) Add 10 ml of vinyl benzyl chloride monomer, 1 ml of N-octyl pyrrolidone and 80 ml of deionized water into a Schlenk tube to prepare a grafting monomer solution, and pass argon gas for 30 minutes to deoxygenate;

[0084] 4) placing the irradiated and frozen HDPE base film into the grafted monomer solution, and continuing to pass argon gas for 2 hours to exhaust oxygen;

[0085] 5) After the Schlenk tube was sealed, magnetic stirring was performed under argon atmosphere, and the temperature was raised to 60° C. for grafting reaction for 4 h;

[0086] 6) After the grafting reaction, the film turns white and is washed in isopropanol for 1 hour and vacuum dried at 50°C for 5 hours;

[0087] 7) placing the grafted HDPE base film into 120 ml NMP solution of 8 g quinuclidine and performing quaternization reaction at 80° C. for 5 days;

[0088] 8) placing the quaternized HDPE base film in a 1M sodium chloride solution for ion exchange for 24 hours;

[0089] 9) The quinine anion exchange membrane after ion exchange is placed in deionized water for cleaning.

[0090] Example 4

[0091] This embodiment provides a method for preparing a PVDF-based quinine-type anion exchange membrane, the specific structure of which is shown below: and the steps are as follows:

[0092]

[0093] 1) The PVDF base film is subjected to electron beam irradiation in air at ≤1 atmosphere; the irradiation energy is 10 MeV and the total dose is 30 kGy;

[0094] 2) storing the irradiated PVDF base film at -40°C;

[0095] 3) Add 20 ml of vinyl benzyl chloride monomer, 1 ml of N-octyl pyrrolidone, and 79 ml of isopropanol into a Schlenk tube to prepare a grafting monomer solution, and pass argon gas for 30 minutes to deoxygenate;

[0096] 4) placing the irradiated PVDF base membrane into the grafting monomer solution and continuing to pass argon gas for 2 hours to exhaust all oxygen;

[0097] 5) After the Schlenk tube was sealed, magnetic stirring was performed under a nitrogen atmosphere, and the temperature was raised to 70° C. for grafting reaction for 8 h;

[0098] 6) After the grafting reaction is completed, the base film is washed in toluene for 1 hour and vacuum dried at 70°C for 4 hours;

[0099] 7) placing the grafted PVDF base membrane into 120 ml NMP solution of 8 g quinuclidine and performing quaternization reaction at 80° C. for 5 days;

[0100] 8) placing the quaternized PVDF base membrane in a 1M sodium chloride solution for ion exchange for 24 hours;

[0101] 9) The quinine anion exchange membrane after ion exchange is placed in deionized water for cleaning.

[0102] Comparative Example 1

[0103] This embodiment provides a method for preparing an ETFE-based piperidine anion exchange membrane, which is carried out according to the following steps:

[0104] 1) The ETFE base film is subjected to electron beam irradiation in air at ≤1 atmosphere; the irradiation energy is 4.5 MeV and the total dose is 100 kGy;

[0105] 2) storing the irradiated ETFE base film at -40°C;

[0106] 3) Add 5 ml of vinyl benzyl chloride monomer, 1 ml of N-octyl pyrrolidone and 94 ml of deionized water into a Schlenk tube to prepare a grafting monomer solution, and pass argon gas for 30 minutes to deoxygenate;

[0107] 4) placing the irradiated ETFE base film into the grafting monomer solution and continuing to pass argon gas for 2 hours to exhaust oxygen;

[0108] 5) After the Schlenk tube was sealed, the temperature was raised to 70°C for grafting reaction for 16 h under nitrogen atmosphere and magnetic stirring;

[0109] 6) After the grafting reaction is completed, wash it in isopropanol for 1 hour and vacuum dry it at 70°C for 5 hours;

[0110] 7) placing the grafted ETFE base film into a 200 ml NMP solution containing 10 g N-methylpiperidine and performing a quaternization reaction at 80° C. for 7 days;

[0111] 8) placing the quaternized ETFE base membrane in a 1M sodium chloride solution for ion exchange for 24 hours;

[0112] 9) Wash the quinine anion exchange membrane after ion exchange in deionized water

[0113] The water absorption rate, water absorption swelling, ion exchange capacity and hydroxide ion conductivity of the pre-irradiated grafted quinine anion exchange membrane prepared in the above examples and comparative examples were tested. The specific data are shown in the following table:

[0114]

[0115]

[0116] The above embodiments and comparative examples synthesize anion exchange membranes based on pre-irradiation grafting with different main chain structures and functional groups. It can be seen from the table that embodiment 1 and embodiment 2 have obvious differences in radiation intensity and grafting conditions, thereby affecting the various properties of the anion exchange membrane. The number of free radicals can be changed by regulating the irradiation intensity, and the number and length of side chains can be changed by regulating the grafting conditions, thereby changing the overall performance of the anion exchange membrane; the difference between embodiment 1 and comparative example 1 is the difference in functional groups. The alkali stability of the quinine type anion exchange membrane is significantly better than that of the piperidine type anion exchange membrane, and the conductivity is higher than that of the piperidine type anion exchange membrane; embodiment 1, embodiment 3, and embodiment 4 select different main chain structures, and the grafting conditions are different, resulting in different performances of the anion exchange membrane finally formed, which proves that different carbon chain polymers can be selected according to the different application scenarios of the anion exchange membrane, and the method for making the quinine type anion exchange membrane of the present invention is applicable to different linear carbon chain polymers. In addition, the anion exchange membranes synthesized by the present invention have high conductivity and strong flexibility. Among them, Example 1 and Example 3 exhibited high hydroxide ion conductivity (>145 mS / cm) and good flexibility (elongation at break>75%).

[0117] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the invention and the claims, all of which fall within the scope of protection of the present invention.

Claims

1. A method for preparing quinine-type anion exchange membrane by pre-irradiation grafting, characterized in that: A linear carbon chain polymer is used as a substrate and a vinyl monomer is used as a grafting monomer. The linear carbon chain polymer is first pre-irradiated with an electron beam radiation source, and then the pre-irradiated substrate is subjected to a grafting reaction in a vinyl monomer solution. The obtained grafted polymer is then subjected to a quaternization reaction with a quinuclidine solution, thereby obtaining a quinine-type anion exchange membrane.

2. The method for preparing quinine-type anion exchange membrane by pre-irradiation grafting according to claim 1, characterized in that: The linear carbon chain polymer is at least one of ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), fluorinated ethylene propylene copolymer (FEP), polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), and hydrogenated styrene butadiene block copolymer (SEBS).

3. The method for preparing quinine-type anion exchange membrane by pre-irradiation grafting according to claim 1, characterized in that: The vinyl monomer is at least one of vinylbenzyl chloride, chloromethylstyrene, undecene bromide and octadecene bromide.

4. The method for preparing quinine-type anion exchange membrane by pre-irradiation grafting according to claim 1, characterized in that: The concentration of the vinyl monomer solution is 5wt.% to 20wt.%, and the solvent is at least one of water, isopropanol, toluene, benzene, and N-methyl-2-pyrrolidone.

5. The method for preparing quinine type anion exchange membrane by pre-irradiation grafting according to claim 1, characterized in that: The irradiation energy of the pre-irradiation is 4.5 MeV to 10 MeV, and the total dose is 30 kGy to 150 kGy.

6. The method for preparing quinine type anion exchange membrane by pre-irradiation grafting according to claim 1, characterized in that: The vinyl monomer solution comprises a surfactant accounting for 10% to 50% of the volume of the vinyl monomer.

7. The method for preparing quinine type anion exchange membrane by pre-irradiation grafting according to claim 1, characterized in that: The concentration of the quinuclidine solution is 3wt.% to 10wt.%.

8. A method for preparing quinine-type anion exchange membrane by pre-irradiation grafting according to any one of claims 1 to 7, characterized in that: The steps include: (1) subjecting the linear carbon chain polymer to electron beam irradiation at ≤1 atmosphere in air or inert gas; storing the irradiated substrate at ≤-40°C; (2) After the vinyl monomer solution in the reactor is deoxygenated by passing an inert gas, the substrate obtained in step (1) is placed in the vinyl monomer solution, and the inert gas is continuously passed into the solution system to exhaust oxygen; (3) sealing the reactor and heating it at a constant temperature to carry out a grafting reaction to prepare a grafted linear carbon chain polymer, wherein the constant temperature heating temperature is 40° C. to 80° C. and the time is 4 h to 16 h; (4) washing the grafted linear carbon chain polymer in a solvent, and drying it in a vacuum drying oven at 50° C. to 80° C. after washing; (5) placing the washed and dried grafted linear carbon chain polymer in a quinuclidine solution at 70° C. to 85° C. for quaternization reaction for 5 to 7 days; (6) After the quaternization reaction, the substrate is washed with water and then placed in a NaCl or NaOH solution at room temperature for ion exchange to obtain a quinine-type anion exchange membrane.

9. The method for preparing quinine-type anion exchange membrane by pre-irradiation grafting according to claim 8, characterized in that: The solvent in step (4) is at least one of water, isopropanol, toluene, ethanol and methanol.

10. A method for preparing a quinine-type anion exchange membrane by pre-irradiation grafting, characterized in that: Obtained by the preparation method as described in any one of claims 1 to 10.

Citation Information

Patent Citations

  • Multi-quaternary ammonium salt anion exchange membrane and its preparation method

    CN102294183A

  • Ion exchange membranes

    CN102753253A

  • Ion exchange film, composition for forming ion exchange film, and production method for ion exchange film

    CN105492508A

  • Single-sheet type bipolar membrane and preparation method thereof

    CN105833737A

  • Homogeneous-phase anion-exchange membrane and preparation method thereof

    CN105903357A